Tingkat Pengetahuan dan Stres Terhadap Siklus Menstruasi Pada Siswi Pondok Pesantren terpadu Babul Magfirah - Fauziah Fauziah; Yadi Putra; Miftahul Khairus (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2024)
Menstruation that is respeate every month eventually forms the menstrual cycle. The menstrual cycle is calculated from the first day of menstruation until exactly one day before the next month’s menstruation. Stress should not be underestimated because it will disrupt the metabolic system in the body. If the metabolism is disturbed, the menstrual cycle also is disturbed. This study uses a descriptive quantitative research design. The population of this study were female students at the Babul Magfirah Integrated Islamic Boarding School Totaling105female students, the sample in the study was 51 people using the Purposive Sampling technique. Data collecton tool the from of a questionnaire whit 51 question that the researchers made themselves. The location of the research was at the Babul Magfirah Integrated Islamic Boarding School on March 13 to 24. The results showed that the level of knowledge and stress on menstruation among students at the Integrated Islamic Boarding School Of Babul Magfirah, the level of knowledge in the high category was 31 respondents (6.8%). Based on the level of high category stress as many as 32 respondents (62.8%). Based on the menstrual cycly level, the normal category was 38 respondents (72.5%). In conclusion, the repondents in this studi had high knowledge and low stress abuot the menstrual cycle. It is recommended that the knowledge level and stress on menstruation collect information from several sources, especially uks officers and teachers to obtain accurate information.